2018
DOI: 10.1609/icwsm.v12i1.15033
|View full text |Cite
|
Sign up to set email alerts
|

Reddit Rules! Characterizing an Ecosystem of Governance

Abstract: The social sharing and news aggregation site Reddit provides a unique example of an ecosystem of community-created rules. Not only do individual subreddits create and enforce their own regulations, but site-wide guidelines and norms may also influence behavior. This paper reports on a mixed-methods study of 100,000 subreddits and their rules. Our findings characterize the types of rules across Reddit, the frequency of rules at scale, and patterns of rules based on subreddit characteristics. We find that rules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(39 citation statements)
references
References 22 publications
3
35
0
1
Order By: Relevance
“…These findings provide concrete evidence supporting prior work's finding on the diversity of moderator activities across subreddits, e.g. (Fiesler et al, 2018;Jhaver et al, 2019b;Seering et al, 2019). Individual-Level Heterogeneity Assumption: Moderators of a given subreddit may perform different activities.…”
Section: Heterogeneous Makeup Of Human Laborsupporting
confidence: 83%
See 1 more Smart Citation
“…These findings provide concrete evidence supporting prior work's finding on the diversity of moderator activities across subreddits, e.g. (Fiesler et al, 2018;Jhaver et al, 2019b;Seering et al, 2019). Individual-Level Heterogeneity Assumption: Moderators of a given subreddit may perform different activities.…”
Section: Heterogeneous Makeup Of Human Laborsupporting
confidence: 83%
“…Team-Level Heterogeneity Assumption: Content moderation work is heterogeneous across subreddits. While large social platforms such as Facebook have focused on developing generalizable tools to facilitate content moderation work, researchers have found that moderators of different communities have different values and approaches to their work (Chandrasekharan et al, 2018;Fiesler et al, 2018;Seering et al, 2019). For example, Fiesler et al (2018) found that communities often express and enforce diverse rules, which imply different moderation practices behind the scenes, Whether this assumption holds has direct implications on what tasks researchers and developers of moderation tools focus on facilitating (Chandrasekharan et al, 2019).…”
Section: Heterogeneous Makeup Of Human Labormentioning
confidence: 99%
“…At the same time, self-governance in online spaces can embrace immense opportunities for institutional flexibility and diversity (De Filippi et al 2020). Despite the shared patterns noted above, rules and norms also differ across communities, even within the same site or platform (Fiesler et al 2018;Chandrasekharan et al 2018;Strimling and Frey 2020). Rules may remain context-dependent and tailored to the community at hand even when they overlap, presumably as a product of diverse community goals, content, membership, technical affordances, and histories.…”
Section: Governance In Multiple Online Communitiesmentioning
confidence: 99%
“…and . Recent analyses that investigate community self-governance practices across a system in a comparative perspective suggest both elements (of similarity and difference), but do not provide insights into how communities' autonomous rules and rule-related activity develops over time (Müller-Birn, Dobusch, and Herbsleb 2013;Chandrasekharan et al 2018;Strimling and Frey 2020;Fiesler et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The author uses negative binomial regressions and negative binomial mixed models to investigate the relationship between users, thread structure, and voting in determining post quality. (Fiesler et al 2018) analyzes rules for community governance and self-organization across a large number of subreddits. (Grover and Mark 2019) presents a systematic study of early indicators for political radicalism in the altright subreddit.…”
Section: Related Workmentioning
confidence: 99%